EXTH-58. THERAPEUTIC HDAC INHIBITION IN HYPERMUTANT DIFFUSE INTRINSIC PONTINE GLIOMA. (12th November 2021) - Noll, Alyssa; Biery, Matt; Myers, Carrie; Paine, Danyelle; Zheng, Ye; Girard, Emily; Winter, Conrad; Morris, Shelli; Brusniak, Mi-Youn; Gottardo, Raphael; Mhyre, Andrew; Foster, Jessica; et al.
Abstract: Diffuse intrinsic pontine glioma (DIPG) continues to carry a dismal prognosis despite a growing understanding of its epigenetic regulation. While generally reclassified as diffuse midline glioma, H3 K27M-mutant (DMG), a subgroup of DIPGs do not harbor the classic histone mutation, with a further subset exhibiting a hypermutant phenotype. To evaluate whether hypermutant DIPG shares transcriptional vulnerabilities with H3K27M-mutant DMG, we screened a biopsy-derived treatment-naive PMS2 mutant DIPG model (PBT-24FH) for sensitivity to a panel of HDAC inhibitors (HDACi). In vitro evaluation of cell viability revealed the low nanomolar IC50 of quisinostat (50nM) and romidepsin (2nM). Dose-dependent increases in H3 acetylation and c-PARP were confirmed by western blot. Despite romidepsin's superior potency in vitro, quisinostat demonstrated greater efficacy in an in vivo PBT-24FH flank study. 42 days following drug initiation, quisinostat-treated mice displayed dramatic tumor regression (mean volume= 33mm 3, n= 7) compared to mice treated with romidepsin (mean volume= 669mm 3, n= 7)(p= 0.005), or vehicle (mean volume= 990mm 3, n= 6)(p< 0.001). Immunohistochemistry of quisinostat-treated tumors revealed few residual tumor cells displaying a low proliferative index. To evaluate cross-resistance, romidepsin-treated mice (mean volume= 1158mm 3, n= 2) were switched to quisinostat treatment and displayed swift tumor regression (mean volume after 25 days of quisinostat= 419mm 3 ), emphasizing quisinostat's in vivo cytotoxic effect against both large tumors and tumors previously treated by another HDACi. To evaluate quisinostat's effect on other hypermutant tumors, we tested HCT-116, a colon cancer cell line bearing a biallelic MLH1 deletion and observed similar cytotoxicity. We also aim to repeat these studies utilizing additional pediatric hypermutant high grade glioma models. Transcriptomic and proteomic investigations are underway to identify the mechanism of action underlying quisinostat-induced cytotoxicity. Ultimately, we are the first to demonstrate in vivo efficacy of the HDACi quisinostat against hypermutant DIPG, supporting further investigation and clinical advancement.